Research on the application of cerebral blood flow reconstruction technology in the surgical treatment of moyamoya disease - Chen, Yuyang; Huang, Chaojue; Wu, Song; Liu, Chang; Luo, Yu; Huang, Litian; Cao, Guan; Liang, Hui; Mo, Panlin; Lu, Jiachao; Su, Xiangsheng; Tong, Xiaoguang; et al. (Frontiers in Surgery, 2026)
PurposeMoyamoya disease (MMD) is characterized by stenosis and occlusion of the cerebral arteries, leading to chronic progressive narrowing at the termini of the bilateral internal carotid arteries (ICA). It represents one of the primary etiologies for both ischemic and hemorrhagic strokes ( 1, 2).Currently, the primary treatment strategy for moyamoya disease (MMD) remains blood flow reconstruction surgery utilizing a bypass from the superficial temporal artery (STA) to the middle cerebral artery (MCA). This approach encompasses direct blood flow reconstruction, indirect blood flow reconstruction, and combined methods of blood flow reconstruction ( 3). However, there remains a paucity of high-quality results from clinical randomized controlled trials. This study aims to summarize the key points, selection criteria, and therapeutic effects of various surgical methods, thereby providing a foundation and accumulating experience for moyamoya disease (MMD) surgery.MethodA retrospective analysis was conducted on the clinical data of adult patients with moyamoya disease who underwent superficial temporal artery-middle cerebral artery + brain-muscle fusion (EMS) combined with blood flow reconstruction (EMS group) and superficial temporal artery-middle cerebral artery + pedicled temporoparietal fascia flap (TPFF) combined with blood flow reconstruction (TPFF group). Summarize and analyze the differences in technical characteristics, clinical efficacy, complications and prognosis between the two surgical methods; A retrospective analysis was conducted on the clinical data of adult patients with moyamoya disease who underwent the double-vessel ST-MCA + EMS group (double-vessel group) and the single-vessel ST-MCA + EMS group (single-vessel group). The technical characteristics, clinical efficacy, complications and prognosis differences of the two surgical methods were summarized and analyzed.ResultThe incidence of postoperative epilepsy in the TPFF group was significantly lower than that in the EMS group (P = 0.043). There were no statistically significant differences between the two groups in terms of postoperative complications, mRS Scores, postoperative bypass patency rate, and Matsushima classification during postoperative follow-up (P > 0.05). There were no significant differences in mRS Scores, anastomotic patency rate of bypass vessels after surgery, CTP perfusion imaging indicators, and Matsushima between the double-vessel group and the single-vessel group (P > 0.05).ConclusionThis study further confirmed that STA-MCA + TPFF is a safe and effective combined blood flow reconstruction surgical method for the treatment of adult MMD, and it has the advantages of less trauma, simple operation, and avoiding adverse reactions caused by temporal muscle application, and can be used for clinical promotion and application. Both double and single STA-MCA + EMS can effectively improve cerebral perfusion in adult MMD patients. Individualized and reasonable choices should be made based on specific conditions.